Managerial Policies for a Quality Madrasa: Uncovering the Management of Teacher Recruitment at Madrasah Aliyah Nahdhatul Ulama (MANU) Banyuputih, Batang Regency - Mochamad Iskarim (Jurnal Hikmatuna, 2019)
This descriptive qualitative research was aimed at investigating teacher-recruitment management attempts that were applied at Madrasah Aliyah Nahdhatul Ulama (NU) Banyuputih, Batang. Teacher recruitment management was vital to assure quality education. The data collections were assembled through interviews and documentation. To analyze the data, this current study applied Miles and Huberman's Interactive Analysis Model. The result of this study showed that Madrasah Aliyah Nahdhatul Ulama (NU) Banyuputih, Batang profoundly implemented effective teacher recruitment management as a starting point to improve quality education. There are several steps in the management of teacher recruitment in the madrasa, namely: determining the criteria for prospective teachers, the source of teacher recruitment, the recruitment method used, calling the teacher candidates accepted, signing work contracts, and involving the foundation management in teacher recruitment. This Madrasa still considers organizational values ​​as an effort to preserve local wisdom and is one of the considerations in the teacher recruitment process. The results of this study are expected to contribute to the scientific management of educational institutions, especially related to the management of qualified teacher recruitment and in accordance with the organization's vision and mission.